The Effect of Integration of STEM Disciplines into Toulmin's Argumentation Model on Students' Academic Achievement, Reflective Thinking, and Psychomotor Skills* - Gülen, Salih; Yaman, S. (Ekip Buro Makineleri A., 2019)
The aim of this research was to examine the effect of integration of STEM disciplines into Toulmin's argumentation model on students' academic achievement, reflective thinking, and psychomotor skills. To be able to get this aim, a quasi-experimental method was used. The participants were 40 sixth grade middle school students divided into two groups, an experimental and a control group with 20 students in each group. The students were at the same achievement level and in a similar socioeconomic status in a public middle school. The experimental group received the treatment in the while the control group received traditional learning of the same topic. The data were collected from academic achievement test, reflective thinking test, and psychomotor observation form. The collected data were analyzed by using Mann Whitney U-test, descriptive analyses (e.g., percentage and frequency), and correlation analyses (Pearson's product moment). According to the data obtained from the measurement tools, it was detected that the integration of STEM disciplines into Toulmin's argumentation model can be used for enhancing the academic achievement of students. It was specified that reflective thinking tendency levels of the experimental group were found to be at a high level. It was also documented that psychomotor skills of experimental group were found to be at a high level. The results suggested that the integration of STEM disciplines into Toulmin's argumentation model can be used for increasing academic achievement of students, developing of the reflective thinking, and observing the development of psychomotor skills at the formation of arguments in the classrooms. © 2019. All Rights Reserved.
Keywords: academic achievement; psychomotor skills; reflective thinking; STEM education; Toulmin's argumentation model